Enhancing numeracy learning among deaf students through BIMA: Design, development, and evaluation of an interactive mobile mathematical sign language application - Ika Santia; Muhammad Najibulloh Muzaki; Aprilia Dwi Handayani; Wasilatul Murtafiah (CV. FOUNDAE, 2026)
Background: Deaf students often encounter challenges in numeracy learning because mathematics instruction is rarely supported by accessible digital media integrating sign language and interactive visual representations. This limitation highlights the need for inclusive mobile learning technologies that accommodate their communication and learning characteristics. Aims: This study aimed to design, develop, and evaluate BIMA (Bahasa Isyarat Matematika), an interactive mobile mathematical sign language application, to enhance numeracy learning among deaf students. Method: This study employed a Research and Development (R&D) approach using the ADDIE model. Data were collected through observations, interviews, expert validation questionnaires, user response questionnaires, and numeracy pre-test and post-test assessments. The data were analyzed using descriptive statistics and N-Gain analysis. Results: The BIMA application achieved a valid level across mathematical content, sign language accuracy, media quality, practicality, and instructional effectiveness, with an overall validation score of 4.05. User responses were highly positive, reaching 96.6%, indicating excellent acceptance and usability. Students’ mean numeracy scores increased from 56.47 to 84.12, with an N-Gain of 0.64, demonstrating a moderate improvement in numeracy achievement. Conclusion: BIMA is a valid, practical, and effective mobile learning application that supports inclusive numeracy education by integrating mathematical sign language, interactive visualization, and mobile technology, offering an innovative approach to improving mathematics learning for deaf students.